Lifestyle Modification in Secondary Prevention: Beyond Pharmacotherapy. (March 2017) - Brinks, Jenna; Fowler, Amy; Franklin, Barry A.; Dulai, Jassu
Despite significant advances in medical technology and pharmacology, cardiovascular disease (CVD) remains a major contributor to health care expenses and the leading cause of death in the United States. Patients with established CVD and their health care providers are challenged with achieving cardiovascular risk reduction to decrease the likelihood of recurrent cardiovascular events. This "secondary prevention" can be achieved, in part, through adherence to prescribed pharmacotherapies that favorably modify major coronary risk factors (ie, hypertension, hypercholesterolemia, diabetes, and obesity). However, lifestyle modification can also be helpful in this regard, providing independent and additive benefits to the associated reductions in cardiovascular morbidity and mortality. Accordingly, physicians and other health care providers should routinely counsel their coronary patients to engage in structured exercise and increased lifestyle physical activity, consume a heart-healthy diet, quit smoking and avoid secondhand smoke, and purposefully address psychosocial stressors that may elevate cardiovascular risk. These lifestyle interventions, either as an adjunct to medication therapy or independently in those patients where medications may be poorly tolerated, cost prohibitive, or ineffective, can significantly decrease cardiovascular mortality and the risk of recurrent cardiac events.